Pooling designs and nonadaptive group testing: important tools for DNA sequencing. - Du, Dingzhu; Du, Dingzhu; Hwang, Frank K (Series on applied mathematics, 2006)
Pooling designs have been widely used in various aspects of DNA sequencing. In biological applications, the well-studied mathematical problem called “group testing” shifts its focus to nonadaptive algorithms while the focus of traditional group testing is on sequential algorithms. Biological applications also bring forth new models not previously considered, such as the error-tolerant model, the complex model, and the inhibitor model. This book is the first attempt to collect all the significant research on pooling designs in one convenient place.